(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
Introduction: Mental disorders are widely recognized as a major contributor to the global burden of disease. Mental illness often generates misunderstanding, prejudice, confusion and fear; therefore it should be a concern for all of us, rather than only for those who suffer from a mental disorder. Aim of this study is to assess the knowledge and attitude on mental illness among people of a selected community. Material And Method: Descriptive cross-sectional research design was used to assess knowledge and attitude in selected community of Biratnagar. Sample size was 92. Non-probability purposive sampling technique was used to collect data through face to face interview using Semi-structured questionnaire. Data entry and analysis was done on SPSS version 16. Descriptive statistics was calculated. Results: Finding of the study shows 88% views mental illness as a medical condition. All respondents identified that mentally ill people cannot held his/her responsibility and are prone to violent. Mental illness perceived as treatable by 66.7% with regular treatment and follow-up and 20.7% preferred treatment with traditional healer. Findings of the study showed adequate level of knowledge among 97.8% respondents. Conclusion: The finding of the study suggests level of knowledge was adequate among respondents whereas most of them had negative attitude towards mental illness. The level of negative attitude suggests the strong emphasis on public education towards mental illness.